The life of Louis XVI - Hardman, John,Ludwig (Yale University Press, 2016)
Parentage and ancestry – Youth on the throne – The bright beginning, 1774-76 – Drift towards war, 1776-78 – War and war finance, 1778-82 – The embarrassments of peace,1783-85 – Unravelling, 1785-86 – Royal revolution: the Assembly of Notables of 1787 – The road to the Estates-General, May 1787 to May 1789 – The king and the Third Estate – The invasion of a palace – The revolution caricatures itself, October 1789 to June 1791 – The flight to Montmedy – Playing by the Book of the Constitution, 13 September 1791 to 10 August 1792 – The prisoner in the Temple
9780300220421
Keywords: Biografie; Louis; Louis XVI 1754-1793